Economic effects of fairs – a complex approach - Kárpáti, László (Applied Studies in Agribusiness and Commerce, 2013)
A complex economic evaluation of fairs / exhibitions can be considered as a novelty in the current literature. In this novel approach, each stakeholder group involved in a fair is evaluated in numerical terms, taking into account the specific cash inflow and outflow categories of that group. The net cash flow is considered as the economic value since it filters out the accumulations. Adding together all the categories, the so-called complex economic value and effectiveness is established regarding the fair surveyed. A numerical model entitled KAVA was developed in order to carry out the calculations for the complex economic effectiveness of the fair. A practical example of using the model is also shown in the paper.